Challenging the Norms Through Language: Unveiling Gender Duality and Identity in Tempest’s Hold Your Own - I Gusti Ayu Sundari Okasunu; Ni Luh Nyoman Seri Malini; Luh Putu Laksminy (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2026)
Language plays a fundamental role in literature, particularly poetry, in shaping and directing the reader’s interpretation of the hidden meaning portrayed by the poet. In regard to this phenomenon, this study examines the construction of gender duality in selected poems written by Tempest in the anthology entitled Hold Your Own through a qualitative content analysis method utilizing retroactive reading and a purposive sampling technique. By juxtaposing the denotative and connotative meaning through the lens of linguistics and literary analysis, this research is theoretically grounded in Riffaterre’s Semiotics and Butler’s Gender Performativity theory. The data consist of thematically and strategically selected lines that reveal nuances of linguistics and literary patterns in representing gender identity. Findings demonstrate that feminime identities are predominantly articulated through lexemes or phrases corelated to softness, passivity, and negative light such as “watching them”, “school bench”, “be kind”, and “witch” meanwhile men are characterized by more assertive, dynamic, and power figure words such as “playing”, “football”, “kick”, “BMW”, and “above her”. The duality of gender is further illustrated through recurrent grammatical deviations such as “how many of yous”, “boy in her”, and “herself top boy” as well as frequent deployment of figurative devices such as simile, paradox, symbolism, hyperbole, and metaphor, one of which is “her shoulder is square”. This study contributes to a deeper understanding of the ways linguistics and narrative strategies in Hold Your Own perform a fluid and complex gender identity, thereby engaging the myth of Tiresias and the contemporary discourse of gender.